1998
DOI: 10.1007/s004120050342
|View full text |Cite
|
Sign up to set email alerts
|

The DNA puff gene BhC4-1 of Bradysia hygida is specifically transcribed in early prepupal salivary glands of Drosophila melanogaster

Abstract: The BhC4-1 gene of the sciarid Bradysia hygida is located at DNA puff C4 and is amplified and actively transcribed in the salivary gland at the end of the last larval instar. We show here that a 3.6 kb fragment from the upstream region of the BhC4-1 gene is able to drive transcription in transgenic Drosophila specifically in prepupal salivary gland in a temporally regulated manner. The mRNA is present in maximal amounts in prepupae +3 h; in prepupae +9 h the levels of BhC4-1 mRNA decline, and it is no longer d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
8

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 38 publications
1
48
0
8
Order By: Relevance
“…DNA was extracted following phenol/chloroform methodology (Monesi et al, 1998) and quantified on 0.8% agarose gels. For all samples, DNA concentration was diluted to 10 ng/µl for further analysis.…”
Section: Pool C (M3+m4+m5+m6)mentioning
confidence: 99%
“…DNA was extracted following phenol/chloroform methodology (Monesi et al, 1998) and quantified on 0.8% agarose gels. For all samples, DNA concentration was diluted to 10 ng/µl for further analysis.…”
Section: Pool C (M3+m4+m5+m6)mentioning
confidence: 99%
“…Extraction and quantification of the DNA genome DNA extraction was carried out using the phenol/chloroform method (Monesi et al, 1998). Samples of muscle tissue, of approximately 100 mg, were ground in liquid nitrogen.…”
Section: Molecular Variability In Brycon Cf Pesumentioning
confidence: 99%
“…The availability of a transformation system and mutant collections, coupled to genomic information in the model system Drosophila melanogaster, prompted us to perform functional assays of DNA puff genes in a transgenic context. In transgenesis, BhC4-1 expression in the salivary glands is a late response to the increase in ecdysone titers at the onset of metamorphosis (Basso et al, 2002;Monesi et al, 1998). Genetic interaction experiments have demonstrated that the products of the ecdysoneinduced early genes, BR-C, E74, and E75 participate to differing extents in the induction of BhC4-1-lacZ in the salivary gland (Basso et al, 2006).…”
mentioning
confidence: 99%